Green Advertising: Environmental Messages in Le Minerale Mineral Water Advertisements - Fira Rizqi Agustina; Naser Ali Abdulghani (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2024)
Until now, waste has been a serious problem for the Indonesian region due to the increasing amount of production. Advertisements are often used as campaign media to influence the public in terms of waste cleanliness, environmental protection and waste recycling. The purpose of this study is to raise public awareness about the importance of protecting and caring for the environment. The discussion in this study includes environmental issues in mineral water advertisements broadcast on television and YouTube channels. In this case, the main subject of discussion is plastic waste, which is a problem for the environment. The hidden meaning behind the Le Minerale mineral water advertisement is revealed by examining each meaning of the images and symbols using Roland Barthes' semiotic analysis with a qualitative method. The data collected is the result of observing and understanding advertisements on YouTube. The results of this study show that the Le Minerale mineral water advertisement uses several symbols to convey its message to the public. By focusing on statements that are expected to create a positive image in the minds of the public. For example, by communicating the advantages of Le Minerale products: the gallon is always new, the cap is airtight and free of viruses. Of course, it also shows a healthy environment, with the intention of showing that Le Minerale products have a good effect on health and the environment.